Model-based classification of regional labour markets: for purposes of labour market policy - Uwe Blien; Franziska Hirschenauer; Phan thi Hong van (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2006)
In many countries fairly large and persistent regional disparities can be observed for a variety of economic indicators. Since these disparities can not be reduced to one single dimension, a classification system is needed to give a parsimonious overview. The article presents a system which is designed to assess labour market policy in Germany. The innovation in this article is the development of a procedure that combines the analysis of determinants of regional disparities with standard classification approaches. The procedure is designed to solve two problems of many existing classification schemes: firstly, their purely descriptive nature and secondly, their interpretation with relation to arbitrarily chosen classification variables. The proposed method is used to identify 12 types which show the regional diversity of labour markets in Germany.
Keywords: R23; R11; R50; 330; Arbeitsmarktforschung; Wirkungsforschung; Arbeitsmarktpolitik; Ausbildungsabsolventen; Berufseinmündung; berufliche Integration; Arbeitslose; regionaler Arbeitsmarkt; regionaler Vergleich; regionale Disparität; Indikatorenbildung; Arbeitsmarktindikatoren; Klassifikation; Klassifikationsmethode; Clusteranalyse; Region - Typologie